Validated finite element analyses of WaveOne Endodontic Instruments: a comparison between M‐Wire and NiTi alloys. (12th July 2014) - Bonessio, N.; Pereira, E. S. J.; Lomiento, G.; Arias, A.; Bahia, M. G. A.; Buono, V. T. L.; Peters, O. A.
Abstract Aim To validate torsional analysis, based on finite elements, of WaveOne instruments against in vitro tests and to model the effects of different nickel–titanium (NiTi) materials. Methodology WaveOne reciprocating instruments (Small, Primary and Large, n = 8 each, M‐Wire) were tested under torsion according to standard ISO 3630‐1. Torsional profiles including torque and angle at fracture were determined. Test conditions were reproduced through Finite Element Analysis (FEA) simulations based on micro‐CT scans at 10‐μm resolution; results were compared to experimental data using analysis of variance and two‐sided one sample t‐tests. The same simulation was performed on virtual instruments with identical geometry and load condition, based on M‐Wire or conventional NiTi alloy. Results Torsional profiles from FEA simulations were in significant agreement with the in vitro results. Therefore, the models developed in this study were accurate and able to provide reliable simulation of the torsional performance. Stock NiTi files under torsional tests had up to 44.9%, 44.9% and 44.1% less flexibility than virtual M‐Wire files at small deflections for Small, Primary and Large instruments, respectively. As deflection levels increased, the differences in flexibility between the two sets of simulated instruments decreased until fracture. Stock NiTi instruments had a torsional fracture resistance up to 10.3%, 8.0% and 7.4% lower than the M‐Wire instruments, for the Small, Primary and Large file, respectively. Conclusion M‐Wire instruments benefitted primarily through higher material flexibility while still at low deflection levels, compared with conventional NiTi alloy. At fracture, the instruments did not take complete advantage of the enhanced fractural resistance of the M‐Wire material, which determines only limited improvements of the torsional performance.